Analisis Kejadian Hipertensi Pada Lansia Di Puskesmas Sukarami Kecamatan Sungai Rotan Kabupaten Muara Enim - Novy Aryani; Ali Harokan; Erma Gustina (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The 2018 Riskesdas shows that the prevalence of hypertension increases with age. A significant increase occurred in the 55-64 year age group, which increased from 3.88% at the age of 45-54 years to 6.29%. The purpose of this study was to determine the factors associated with the incidence of hypertension in the elderly at the Sukarami Health Center, Sungai Rotan District, Muara Enim Regency in 2023. The design of this study was a quantitative cross-sectional approach. The population in this study is the people who seek treatment at the Sukarami Health Center, Sungai Rotan District, Muara Enim Regency in 2023 totaling 2,968 respondents. The sample in this study amounted to 97 respondents. How to take samples using purposive sampling. This research was carried out from June 20 2023 to July 5 2023. Data collection used a questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between age (p value 0,000), body weight (p value 0,000) and the role of officers (p value 0,000) with the incidence of hypertension in the elderly at the Sukarami Community Health Center, Sungai Rotan District, Muara Enim Regency in 2023. There was no relationship between gender (p value 0,821), smoking status (p value 1,000) and diabetes mellitus with the incidence of hypertension in the elderly at the Sukarami Health Center, Sungai Rotan District, Muara Enim Regency in 2023. Provide health education about hypertension and risk factors for hypertension in the elderly